(untitled) (Proceedings of International Educators Conference, 2022)
In this article, special attention is paid to the fact that Mahmud Kashgari-ibn Husayn ibn Muhammad is known as the founder of the science of Turkic studies, an encyclopedist scientist, therefore, attempts were made to analyze and study his scientific heritage from different perspectives. As a result of this, a whole group like Kashgarian studies was formed. It is explained that the composition of this group is mainly composed of linguists, orientalists, historians, art historians, ethnographers, and even geographers.